STRATEGI JASA ANGKUTAN DAMRI TRAYEK SERPONG KE BANDARA SOEKARNO-HATTA - Hendro Kuntohadi; Dimas Tri Erlangga; Deden Galih Ginanjar (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of this research is to find out the strategy of Damri transport service route Serpong – Soekarno Hatta International Airport. The method used SWOT analysis using IE (Internal-External) matrix, IFE (Internal Factor Evaluation) which has total score of 3.51 and  EFE (External Factor Evaluation) with total score of 3.55. Samples taken from 8 (eight) staff of PERUM DAMRI in Soekarno Hatta Airport branch. It is in quadrant I of IE matrix which still increase and advance. The strategies needed to be applied are market elaboration and product development. Based on SWOT analysis using internal and external table analysis, the route is in quadrant I which has the Strength score of 4.07 and the Weakness score of 2.55 that create the difference of those internal factors of 1.52. On the other hand, the Opportunity score is 3.86 and the Threat score is 3.23 that construct the difference of those external factors of 0.63. The conclusion is the company is in solvent position that has positive strength and opportunity. The company could apply S-O strategy of SWOT matrix which uses the most of strength and opportunity factors.